THE ROLE OF PHONETIC STYLISTIC DEVICES IN IMPROVING ORAL SPEECH IN ENGLISH - Saideksonova Moxichexra Ulug‘bek qizi (International Journal of Literature and Language Studies, 2026)
This article examines the role of phonetic stylistic devices in improving oral speech in English. It explores how such devices as alliteration, assonance, consonance, rhyme, rhythm, intonation, stress, and repetition contribute to the development of learners' pronunciation, fluency, and expressive speaking skills. The study is based on theoretical analysis and examples from English speech and literature. The findings indicate that the effective use of phonetic stylistic devices enhances speech clarity, communicative competence, listening comprehension, and overall oral performance. The article emphasizes the importance of integrating phonetic stylistic devices into English language teaching to improve learners' speaking proficiency.